Laboratory guide to medical physiology - Ostatníková, Daniela, 1957- (Vydavateľstvo UK, 2018)
This guide was prepared to help students perform various experiments and examinations and to learn and apply the knowledge of practical physiology into clinical medicine. In the past the use of living animals has been routine practice in the medical training curriculum. Recently, due to ethical issues, we have had to replace animals with non-animal alternatives. The new attempts have been introduced to our experimental medical physiology teaching and the students learn on virtual animals in virtual labs. The interactive computer programmes provide the possibility to learn with one's own pace, stop the experiment any time, review the results, and switch to another experiment during the practical classes. The material can help medical student to organize his/her thinking and provide practical aspect of studied material in particular area of physiology.